Pengaruh dukungan sosial terhadap tingkat kecemasan masa depan siswa dalam persiapan masuk perguruan tinggi - Ratno, Shinta Belinda; Damayanti, Desita Dyah; Astuti, Tri (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Anxiety about the future is a phenomenon often experienced by high school students, especially when preparing to continue their education in college. Feelings of fear of failing to enter their dream college, difficulty adapting, and uncertainty about future prospects often cause disturbing psychological and physical symptoms. Social support from family, friends, and the environment is believed to be able to reduce these anxiety levels. Purpose: To determine the influence of social support on students' future anxiety levels in preparation for entering college. Method: The study used quantitative methods with purposive sampling techniques. The research sample consisted of 146 high school students aged 15–18 years who wished to continue their studies at university. The instruments used were a social support scale with a Cronbach's Alpha reliability of 0.929 and a future anxiety scale with a reliability of 0.915. Data analysis was performed using simple linear regression. Results: The study indicate a significant negative correlation between social support and future anxiety (sig. 0.000; p < 0.05). The correlation coefficient is 0.523 with a coefficient of determination of 0.273, which means that social support contributes 27.3% to the reduction in anxiety, while 72.7% is influenced by other factors. The regression coefficient (B) of -0.659 confirms that the higher the social support received by students, the lower their anxiety levels. Conclusion: Social support plays an important role in reducing high school students' anxiety about the future. This study provides a theoretical contribution regarding the relationship between social support and anxiety, as well as practical guidance for parents, teachers, and the surrounding community in providing optimal support to students who are preparing to enter college. Suggestion: For future researchers, they can add broader topics or add variables that may be related to the two variables in this study. Keywords: Anxiety; Social Support; Students. Pendahuluan: Kecemasan masa depan merupakan fenomena yang sering dialami siswa SMA, terutama saat mempersiapkan diri untuk melanjutkan pendidikan ke perguruan tinggi. Perasaan takut gagal masuk kampus impian, kesulitan beradaptasi, maupun ketidakpastian prospek masa depan sering menimbulkan gejala psikologis dan fisik yang mengganggu. Dukungan sosial dari keluarga, teman, maupun lingkungan diyakini mampu menurunkan tingkat kecemasan tersebut. Tujuan: Untuk mengetahui pengaruh dukungan sosial terhadap tingkat kecemasan masa depan siswa dalam persiapan masuk perguruan tinggi. Metode: Penelitian kuantitatif dengan teknik purposive sampling. Sampel penelitian berjumlah 146 siswa SMA berusia 15–18 tahun yang berkeinginan melanjutkan studi ke perguruan tinggi. Instrumen yang digunakan berupa skala dukungan sosial dengan reliabilitas Cronbach’s Alpha 0.929 dan skala kecemasan masa depan dengan reliabilitas 0.915. Analisis data dilakukan menggunakan regresi linear sederhana. Hasil: Menunjukkan adanya pengaruh negatif yang signifikan antara dukungan sosial dan kecemasan masa depan (sig. 0.000; p < 0.05). Koefisien korelasi sebesar 0.523 dengan koefisien determinasi 0.273, berarti dukungan sosial berkontribusi 27.3% terhadap penurunan kecemasan, sedangkan 72.7% dipengaruhi faktor lain. Koefisien regresi (B) sebesar -0.659 menegaskan bahwa semakin tinggi dukungan sosial yang diterima siswa, semakin rendah tingkat kecemasannya. Simpulan: Dukungan sosial memainkan peran penting dalam menurunkan kecemasan masa depan siswa SMA. Penelitian ini memberikan kontribusi teoritis mengenai keterkaitan dukungan sosial dan kecemasan, serta menjadi rujukan praktis bagi orang tua, guru, dan lingkungan sekitar dalam memberikan dukungan optimal kepada siswa yang sedang mempersiapkan diri masuk perguruan tinggi. Saran: Bagi peneliti selanjutnya, dapat menambahkan topik yang lebih luas lagi ataupun menambahkan variabel yang mungkin berkaitan dengan dua variabel pada penelian ini. Kata Kunci: Dukungan Sosial; Kecemasan; Siswa.